A Mathematical Model of the Transmission Dynamics and Control of Bovine Brucellosis in Cattle - Stephen Abagna; Baba Seidu; C. S. Bornaa (Abstract and Applied Analysis)
Brucellosis is one of the most serious diseases that wreaks havoc on the production of livestock. Despite various efforts made to curb the spread of brucellosis, the disease remains a major health concern to both humans and animals. In this work, a deterministic model is developed to investigate the transmission dynamics and control of bovine brucellosis in a herd of cattle. The disease-free equilibrium point of the model is shown to be locally asymptotically stable whenever basic reproduction number R0≤1 and unstable if R0>1. Also, the endemic equilibrium point of the model is shown to be locally asymptotically stable whenever R0>1 and unstable otherwise. Numerical simulations of the model suggest that vaccination is the most efficient single control intervention. Also, the most efficient pair of control interventions is vaccination and culling of seropositive cattle. However, the best way to control bovine brucellosis in cattle is the combination of the three control interventions (vaccination, culling of seropositive cattle, and observation of comprehensive biosecurity protocols).